Servidor VoIP com sistema de segurança doméstica integrada de baixo custo - Destefani, Felipe Augusto (2013)
This project aims to develop a low cost home VoIP system. The methodology consists in specifying the project, starting by learning this projects importance to the potential clients and product final users, then modeling and defining solutions with the specified functionalities, implementing and integrating the various modules which compose the whole system to then validate the prototype and finish the project, gathering information from all parts along the project development. The final product, Fly-IP has various cells with various possible functionalities, but there are two main cells composed by two servers which communicate between themselves. The first server works with VoIP communication, it will cover the telephony part of the system with the majority of the possible operations from the actual telephony. The second server will communicate with the first making an interface with various possible control entities, for example, a system user may use his own cellphone to open his house entrance.